Use of the zebrafish model for target identification for host-directed therapies against tuberculosis - Larsson, Simon (Nanyang Technological University, 2024)
Tuberculosis is one of the deadliest infectious diseases in the world. It is exacerbated by the rise of multi-drug resistant strains. Host-directed therapies are an innovative approach by targeting host pathways to enhance immunity and suppress bacterial replication. The work described in this thesis makes use of the zebrafish model to investigate potential target pathways for host directed therapies against tuberculosis. The first section of focuses on understanding the role of the Hedgehog signaling pathway in the immune response to mycobacterial infection. I demonstrate that modulating the activity of this pathway affects the progression of infection in zebrafish larvae. I also showed that human macrophages secrete functional Sonic Hedgehog in response to mycobacterial infection, regulated by the transcription factor Stat6. The second section explores a natural product screen that identified a marine extract, JM3-1, which disrupts vascular development in zebrafish embryos. While JM3-1 induced vascular defects, such as angiogenic hyper-sprouting and edema, it did not impact bacterial burden in M. marinum infections, suggesting its effects are independent of host-pathogen interactions. Overall, this thesis highlights the zebrafish as a powerful model for identifying novel host targets and screening potential therapeutic compounds. The discoveries made herein offer important insights into the role of host signaling pathways in tuberculosis, offering potential avenues for future development of host-directed therapies.